Scars for Life(s) - Jessica Suzanne Stokes (Current Objectives of Postgraduate American Studies)
This essay explores the relationship between performance, disability, and the ephemera of traumatic experience by using the bodily scar as a focal point for multi-temporal and multi-spatial reflection.